The Effect of Reward & Recognition Toward Employees’ Job Satisfaction & Job Performance in Kantor Pelayanan Pajak Pratama Mempawah - admin, Erwin Bastian B12112007 (Jurnal Manajemen Update, 2016)
The increase of competitive environment among service industries have madeorganizations perform their best in order to achieve assigned goals and targets.Organizations’ performance are rely on their human resources. One of many ways that canbe adopting and implementing to make employees perform well is the set of operationmanagement practices is Compensation. Compensation is one of the best forms of operationmanagement practices which receive a great attention in business world.Keywords: Compensation, reward, recognition, employees’ job satisfaction, employees’ jobperformance